World enough, and time : the travel chronicles of Mrs. J. Theodore Bent. - Bent, Theodore, Mrs., -1929, (Archaeopress travel ;, 2006)
This work chronicles the Greek journeys of Mabel, Mrs J. Theodore Bent.